An unexpected peril - Raybourn, Deanna (Raybourn, Deanna. Veronica Speedwell mystery, 2021)
"A princess is missing and a peace treaty is on the verge of collapse in this new Veronica Speedwell adventure from the New York Times bestselling and Edgar® Award-nominated author Deanna Raybourn. January 1889. As the newest member of the Curiosity Club--an elite society of brilliant, intrepid women--Veronica Speedwell is excited to put her many skills to good use. As she assembles a memorial exhibition for pioneering mountain climber Alice Baker-Greene, Veronica discovers evidence that the recent death was not a tragic climbing accident but murder. Veronica and her natural historian beau, Stoker, tell the patron of the exhibit, Princess Gisela of Alpenwald, of their findings. With Europe on the verge of war, Gisela's chancellor, Count von Rechstein, does not want to make waves--and before Veronica and Stoker can figure out their next move, the princess disappears. Having noted Veronica's resemblance to the princess, von Rechstein begs her to pose as Gisela for the sake of the peace treaty that brought the princess to England. Veronica reluctantly agrees to the scheme. She and Stoker must work together to keep the treaty intact while navigating unwelcome advances, assassination attempts, and Veronica's own family--the royalty who has never claimed her"--